Caveats and pitfalls associated with researching community engagement in the context of HIV vaccine trials. (January 2020) - Kagee, Ashraf; De Wet, Anneliese; Kafaar, Zuhayr; Lesch, Anthea; Swartz, Leslie; Newman, Peter A
HIV vaccine efficacy trials require the enrolment of large numbers of HIV-negative individuals and thus it is necessary to engage with communities where HIV incidence is high. We identify some of the caveats and pitfalls associated with researching community engagement in the context of HIV vaccine trials. These are as follows: the lack of consensus of what community engagement is and how it is practiced, the sometimes paradoxical role of community advisory boards as community representatives and challenges associated with information dissemination in communities. We identify a set of considerations for community engagement practitioners, trial investigators and social scientists when conducting community engagement.